Links between teachers’ attachment style and social interest - Kepalaitė, Albina (Social Welfare: Interdisciplinary Approach, 2012)
Quality of teachers’ and pupils’ relationships is related to peculiarities of teachers’ attachment and social interest. The dominating teachers’ insecure attachment style was identified. Female teachers more often distinguish themselves by secure and disorientated attachment style, while male teachers more often distinguish themselves by preoccupied and dismissive attachment styles. Female teachers distinguish themselves by both high and medium social interest whilst male teachers, by medium and low social interest. The majority of teachers with secure attachment style distinguish themselves by high social interest. It is assumed that there are factors that can influence the interaction between social interest and attachment style.